(untitled) (Discourse of Law and Administration, 2024)
The notary carries out the tasks of the state, while guaranteeing the safety of trading. It performs public tasks granted by the state in specific social, political or economic conditions, which makes it necessary for the legislator to monitor the catalog of activities entrusted to notaries to perform and adapt them to the current needs of society in order to ensure the safety of trading. The state, adressing the need to influence legal relations important from the point of view of the state’s interests, makes the achievement of the legal effect intended by the parties dependent on the participation of a notary public as a person of public trust that guarantees the security of trading. When analyzing the catalog of notarial activities after 1991, one can notice a gradual expansion of notaries’ competences. The legislator has entrusted them with new notarial activities, not only in the field of civil law transactions, but also non-contentious activities previously reserved exclusively for the activities of courts.